Samtidspuls — om hälsobegreppets revitaliserande innebörder - Winroth, AnnCristin (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2003)
Contemporary notions of health are discussed in relation to social movements and as an expression of a growing medical pluralism. In the attempt to take the pulse of general debates on health, a tesselated picture of today's society appears. In rapid succession, themes about a growing number of elusive health problems and sick-listings appear from a working life that is termed stressful, fickle, and constantly lacking in time. Further, there are discussions that illustrate the confidence in new pharmaceuticals, in the benefits of biogenetic research, and the good future that is promised by them. Since the middle of the 1990s there are increasingly features on so called alternative treatments, which in their turn claim to show the way to a better life. By calling for individual body awareness, extended self-treatment, a calmer pace and the need for rest and reflection in a much too pressured and splintered daily life, modern man hopes to increase resistance to the side-effects of modern life styles. Hence, health is a plastic, spacious concept that holds a consistent understanding as well as a sensitivity to trends and potential for change. Lack of health is considered a threat in the present-day as well as in past societies.